2004
DOI: 10.1158/1078-0432.ccr-0991-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Cell-Free Epstein-Barr Virus DNA in Plasma of Patients with Nonnasopharyngeal Head and Neck Carcinomas

Abstract: Purpose: We investigated the detectability of EBV DNA in the plasma of patients with non-nasopharyngeal head and neck carcinomas (NNHNC). Previous studies have shown that EBV is present in the tumor tissue of some NNHNC.Experimental Design: We recruited 101 patients with NNHNC and 48 healthy controls. Blood samples were taken from controls and patients before treatment. Tumor tissue samples were tested for the presence of EBV in the first 69 patients by in situ hybridization for small EBV-encoded RNA (EBER). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
7
13
1
1
Order By: Relevance
“…However, some of our patients with EBER-negative tumor cells demonstrated low levels of EBV DNA in their plasma. This finding corresponds to a previous report showing a slight increase in plasma EBV DNA in a significant proportion of patients with EBER-negative squamous cell carcinoma of the head and neck regions (Yu et al, 2004). Additionally, three patients in our study who had undetectable EBV genome in tumor cells and circulating lymphocytes showed EBV DNA in the plasma (29 copies/ml, 69 copies/ml, and 920 copies/ml).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, some of our patients with EBER-negative tumor cells demonstrated low levels of EBV DNA in their plasma. This finding corresponds to a previous report showing a slight increase in plasma EBV DNA in a significant proportion of patients with EBER-negative squamous cell carcinoma of the head and neck regions (Yu et al, 2004). Additionally, three patients in our study who had undetectable EBV genome in tumor cells and circulating lymphocytes showed EBV DNA in the plasma (29 copies/ml, 69 copies/ml, and 920 copies/ml).…”
Section: Discussionsupporting
confidence: 92%
“…A high level of cell-free EBV DNA in plasma was detected in patients with EBV-associated disease such as nasopharyngeal carcinoma, Hodgkin's lymphoma, extranodal NK-T-cell lymphoma, nasal type, post-transplant lymphoproliferative disease, Burkitt's lymphoma, lymphoepithelial carcinoma, and infectious mononucleosis (Chan et al, 2003;Gallagher et al, 1999;Green et al, 1998;Lei et al, 2000Lei et al, , 2002Lit et al, 2004;Lo et al, 1999;Yu et al, 2004). The concentration in positive samples varied from 24 copies/ml to more than 600,000 copies/ml, while the samples from healthy individuals were usually negative.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that DNA alterations in tumour tissue can be detected in blood using cfDNA [2,3,[7][8][9][10][11]. However, the fraction of tumour-origin DNA in cfDNA can be very low since cfDNA is derived from both tumour and non-tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the use of circulating free DNA (cfDNA) from plasma or serum as an alternative and additional source of DNA to test cancer specific genetic alterations is an attractive proposition [5,6]. Recent advances in PCR (Polymerase Chain Reaction) based technology have allowed the analysis of specific genetic (point mutations in EGFR [7,8], KRAS [8], BRAF [9]) and epigenetic alterations (such as HPV [10] and EBV [11]) in cfDNA isolated from patients' plasma or serum. These genes are of particular importance in determining the response to a variety of novel agents in clinical use and in the development of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have indicated a good correlation between restricted expression at the tissue level and the occurrence of detectable levels of candidate biomarkers in serum/plasma DNA. In this connection, the circulating methylated DNA approach has been applied as a biomarker in various forms of cancer, including pancreatic [19,20,24,25], ovarian [26][27][28][29], prostate carcinoma [30][31][32][33][34], hepatocellular carcinoma [35][36][37][38], esophageal adenocarcinoma [39,40], colorectal carcinoma [8,41,42], breast [3,[43][44][45], head and neck squamous cell carcinoma [46][47][48], non-Hodgkin lymphoma [49], and lung cancer [10,16,18,[50][51][52].…”
Section: Altered Epigenetic Regulation Assessed By the Cell-free Circmentioning
confidence: 99%